G-110 Events in early HIV-1 infection that prime the development of heterologous neutralization breadth. (March 2017) - Derdeyn, Cynthia
Abstract : A recent IAVI study reported that viral load, HLA-A*03, and subtype C HIV-1 were strongly associated with the development of neutralization breadth in a multi-site African cohort. Here, we investigated the impact of early autologous neutralization and envelope (Env) diversification in subjects in Kigali, Rwanda (n = 9) and Lusaka, Zambia (n = 12), in conjunction with correlates from the parent cohort. Our analysis revealed that potent neutralization against the transmitted/founder (T/F) Env and extensive Env diversification leading to viral escape within 4–8 months from infection were vital components for the development of breadth, demonstrating priority over the population-based correlates. To gain further insight into how early antibodies against the T/F Env influence breadth, we characterized 75 monoclonal antibodies (mAbs) from the top neutralizer and 74 mAbs from a poor neutralizer. The mAbs were recovered from single memory B cells tagged by the autologous T/F gp120 protein. Examination of germline usage revealed that the anti-gp120 mAbs in both individuals (and in 2 others) utilized numerous heavy chain germline lineages that have been associated with bnAb activity, suggesting that these are generic responses. mAbs from the poor neutralizer were significantly more clonal, more somatically mutated, had longer CDRH3s, and bound with higher affinity (KD) to the autologous T/F gp120 protein than those from the top neutralizer. Together, these studies highlight the complexity of the development of neutralization breadth from early autologous antibodies during HIV-1 infection, and challenge the concept that activation of a particular germline or driving common bnAb-associated attributes will necessarily lead to bnAbs.